The courage to be - Tillich, Paul, 1886-1965 (Yale Nota bene., 2000)
The great Christian existentialist thinker Paul Tillich describes the dilemma of modern man and points a way to the conquest of the problem of anxiety. This edition includes a new introduction by Harvey Cox that situates the book within the theological conversation into which it first appeared and conveys its continued relevance in the current century.